Misrepair in Context: TGFβ Regulation of DNA Repair - Liu, Qi; Lopez, Kirsten; Murnane, John; Humphrey, Timothy; Barcellos-Hoff, Mary Helen (Frontiers in Oncology, 2019)
Repair of DNA damage protects genomic integrity, which is key to tissue functional integrity. In cancer, the type and fidelity of DNA damage response is the fundamental basis for clinical response to cytotoxic therapy. Here we consider the contribution of transforming growth factor-beta (TGFβ), a ubiquitous, pleotropic cytokine that is abundant in the tumor microenvironment, to therapeutic response. The action of TGFβ is best illustrated in head and neck squamous cell carcinoma (HNSCC). Survival of HNSCC patients with human papilloma virus (HPV) positive cancer is more than double compared to those with HPV-negative HNSCC. Notably, HPV infection profoundly impairs TGFβ signaling. HPV blockade of TGFβ signaling, or pharmaceutical TGFβ inhibition that phenocopies HPV infection, shifts cancer cells from error-free homologous-recombination DNA double-strand-break (DSB) repair to error-prone alternative end-joining (altEJ). Cells using altEJ are more sensitive to standard of care radiotherapy and cisplatin, and are sensitized to PARP inhibitors. Hence, HPV-positive HNSCC is an experiment of nature that provides a strong rationale for the use of TGFβ inhibitors for optimal therapeutic combinations that improve patient outcome.